Antibody cooperative adsorption onto AuNPs and its exploitation to force natural killer cells to kill HIV-infected T cells. (February 2021) - Astorga-Gamaza, Antonio; Vitali, Michele; Borrajo, Mireya L.; Suárez-López, Rosa; Jaime, Carlos; Bastus, Neus; Serra-Peinado, Carla; Luque-Ballesteros, Laura; Blanch-Lombarte, Oscar; Prado, Julia G.; Lorente, Juan; Pumarola, Felix; et al.
Highlights: We generate a new nanotool consisting of bispecific nanoparticles with cooperatively-adsorbed antibodies at their surface. No modification of antibodies or addition of linkers are required. p BiAb-AuNPs are useful for cell-to-cell engagement and boosting the immune response. Specifically, our p BiAb-AuNPs reinvigorate the Natural killer cell immune function towards HIV. Beyond HIV, this technology might represent a new platform with applicative prospective in nanotechnology and immunotherapy. Graphical Abstract: ga1 Abstract: HIV represents a persistent infection which negatively alters the immune system. New tools to reinvigorate different immune cell populations to impact HIV are needed. Herein, a novel nanotool for the specific enhancement of the natural killer (NK) immune response towards HIV-infected T-cells has been developed. Bispecific Au nanoparticles (BiAb-AuNPs), dually conjugated with IgG anti-HIVgp120 and IgG anti-human CD16 antibodies, were generated by a new controlled, linker-free and cooperative conjugation method promoting the ordered distribution and segregation of antibodies in domains. The cooperatively-adsorbed antibodies fully retained the capabilities to recognize their cognate antigen and were able to significantly enhance cell-to-cell contact between HIV-expressing cells and NK cells. As a consequence, the BiAb-AuNPs triggered a potent cytotoxic response against HIV-infected cells in blood and human tonsil explants. Remarkably, the BiAb-AuNPs were able to significantly reduce latent HIV infection after viral reactivation in a primary cell model of HIV latency. This novel molecularly-targeted strategy using a bispecific nanotool to enhance the immune system represents a new approximation with potential applications beyond HIV.